Due interviste a Massimo Fagioli - Fagioli, Massimo (Il sogno della farfalla, 2024)
In these two interviews, aired in 1998 and 2002, Massimo Fagioli critically confronts anti-psychiatric culture and practice, in particular that of Franco Basaglia, denouncing its structural and theoretical limits. Through the account of his own personal research, and the analysis of the Italian social and health condition, Fagioli proposes his approach to psychiatric research and treatment of mental illness, clearly distinct from mere assistance.